2020
DOI: 10.1111/odi.13255
|View full text |Cite
|
Sign up to set email alerts
|

RORγt antagonist improves Sjögren's syndrome‐like sialadenitis through downregulation of CD25

Abstract: Objective We reported previously that T‐cell‐specific RORγt‐transgenic mice under human CD2 promoter (RORγt‐Tg mice) developed severe spontaneous Sjögren's syndrome (SS)‐like sialadenitis, induced by RORγt‐overexpressing CD4+T cells and reduced regulatory T cells. The purpose of this study was to clarify the effectiveness and mechanisms of action of A213, a RORγt antagonist, in RORγt‐Tg mice with SS‐like sialadenitis. Methods Six‐week‐old RORγt‐Tg mice were administered orally of A213 or phosphate‐buffered sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The presence of activated T cells (CD3 + CD25 + or CD3 + CD69 + cells) and Th cells (CD4 + CD25 + or CD4 + CD69 + cells) was investigated as described previously [35,36]. Moreover, RORγ-transgenic mice, an established SS-like sialadenitis mice model, were reported to induce the expression of IL-2-mediated CD25 and CD69 on CD4 + T cells [37].…”
Section: Flow Cytometric Analysis For Activated T Cellsmentioning
confidence: 99%
“…The presence of activated T cells (CD3 + CD25 + or CD3 + CD69 + cells) and Th cells (CD4 + CD25 + or CD4 + CD69 + cells) was investigated as described previously [35,36]. Moreover, RORγ-transgenic mice, an established SS-like sialadenitis mice model, were reported to induce the expression of IL-2-mediated CD25 and CD69 on CD4 + T cells [37].…”
Section: Flow Cytometric Analysis For Activated T Cellsmentioning
confidence: 99%
“…Our work demonstrated that the stimulation of naïve CD4 + T cells with either Pam 3 CSK 4 in co-cultures or Th17 polarizing reagents resulted in the most profound increase in CD25 expression; RvE1 significantly decreased this under T h 17 polarizing conditions. This finding was in parallel with a significantly reduced IL-2 cytokine secretion by T cells under the same conditions by the RvE1, which may suggest that RvE1 suppressed IL-2 secretion leading to a decrease of CD25 expression ( 66 ). CD4 + CD25 + T cells are known as “natural suppressor cells,” showing anergic, suppressing functions by inhibiting transcription of IL-2 via TCR, Exposing to antigen stimulation or polyclonal T cell receptor stimulation activates these cells (CD4 + CD25 + ) to mediate their suppressive functions ( 67 , 68 ), which may be the reason for increased CD4 + CD25 + T cell populations under Th17 polarizing conditions and DC-mediated Th17 polarization.…”
Section: Discussionmentioning
confidence: 73%
“…Treatment of SS animal models demonstrated that administering an analogue of B7-H4 -a co-stimulatory molecule involved in the promotion of Treg cells activity and whose blockade is known to worsen multiple models of autoimmune diseases -was able to reduce lymphocyte infiltration in salivary glands and an expansion of Treg cells (110). Disease improvement was also demonstrated by inhibiting bone morphogenetic protein (BMP)-6, highmobility group box (HMGB)1 (which have both been associated to reduced salivary secretion (110,111)), and transcription factor RAR-related orphan receptor (ROR)γt (112). Some in vitro evidence suggests that Janus kinase (JAK) inhibitors may be effective in SS by modulating DNA hydromethylation induced by IFNs and reactive oxygen species (113).…”
Section: New Insights In Ss Treatmentmentioning
confidence: 99%